Control of bacterial cells growths by magnetic hyperthermia - Bañobre-López, M. (2013)
In this work, we report the effectiveness of magnetic hyperthermia as a potential disinfection method against food spoilage microorganisms. High structural-magnetic quality magnetite nanoparticles have been found to be effective against bacterial microorganisms in solution under an oscillating magnetic field. Samples containing both magnetite nanoparticles and Pseudomonas fluorescens cells in aqueous solution have been subjected to an alternating magnetic field of chosen amplitude 100 Oe with frequency of 873 kHz for different times, achieving different maximum temperatures ranging from 35°C to 55°C. The subsequent colony forming units count evidenced an important decreasing of the cell survival with temperature in comparison to a conventional direct heating, ending in the total eradication of the microorganisms in relatively short times (~8 min). This ability of magnetic hyperthermia to control bacteria cells constitutes a novel contribution to the finding of new useful applications of hyperthermia different from biomedicine.